Norman MacCaig and the fascination of existence - Ingrassia, Nathalie Sylvie (The University of Edinburgh, 2014)
This thesis is a comprehensive study of the poetry of Norman MacCaig. His poems have received relatively little critical attention and scholars appear to have concentrated on a few specific points such as MacCaig’s characteristic restraint or his inscription in a given literary tradition. Critics have notably pointed out different dichotomies in his works. I argue that these dichotomies are fundamentally interrelated. It is characteristic of MacCaig’s writing to simultaneously engage with and challenge philosophical and linguistic concepts and positions as well as literary traditions and stylistic choices. These dichotomies are both a cause and a symptom of this phenomenon. They take on a structuring role in a body of works often regarded as a collection of independent lyrics rather than a cohesive totality. The first half of the thesis will follow a thematic approach: considering first the poetic project MacCaig outlines and the interplay of celebration, faithfulness to the object and the problem of perception; then the treatment of religion and the divine by this notoriously atheist author and how it relates to his worldview. This will provide a basis to address MacCaig’s lifelong concern with the relationship between perception, language and description and what this entails for both his writing and his philosophical positions. In the second half of this study, I will address MacCaig’s engagement with tradition – and its limits – through consideration of three different modes and how they relate to his writing project: elegy, pastoral and amatory verse, regarding the latter two as specific examples of the former. Through these interconnected studies of MacCaig’s poetry, I argue that the critical tendency to either undervalue his central place or treat his works in a fragmentary fashion originates in MacCaig’s sense of the instability of our perceptions and our possible discourses about the world. This uncertainty at the root of his writing reflects his constant and often uncomfortable awareness of the elusive nature of existence and meaning – death and the limits of language threatening both his perception of the world he evinces such fondness for and his ability to write about it.
Keywords: MacCaig, Norman; Scottish poetry